2022
DOI: 10.1186/s12913-022-07489-2
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of value-based healthcare: a scoping review

Abstract: Background The aim of this study was to identify and summarize how value-based healthcare (VBHC) is conceptualized in the literature and implemented in hospitals. Furthermore, an overview was created of the effects of both the implementation of VBHC and the implementation strategies used. Methods A scoping review was conducted by searching online databases for articles published between January 2006 and February 2021. Empirical as well as non-empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 86 publications
(190 reference statements)
2
44
0
1
Order By: Relevance
“…The lack of implementation articles was in line with other research in hospital settings; Reitblat et al concluded that the implementation and investigation of the strategic agenda in urology was limited 21 and another scoping review specifically focusing on VBHC implementation in hospital settings showed the same scarcity. 22 One reason for the lack of implementation articles might be the absence of a practical implementation guide for VBHC. The need for a roadmap that addresses the required steps for organisational changes has been acknowledged before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of implementation articles was in line with other research in hospital settings; Reitblat et al concluded that the implementation and investigation of the strategic agenda in urology was limited 21 and another scoping review specifically focusing on VBHC implementation in hospital settings showed the same scarcity. 22 One reason for the lack of implementation articles might be the absence of a practical implementation guide for VBHC. The need for a roadmap that addresses the required steps for organisational changes has been acknowledged before.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to date, hardly any reviews on VBHC have been published, and existing reviews focusing on, for example, articles with an implementation of VBHC. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has found widespread success in modern healthcare management (1), and value dimensions are widely represented among the performance dimensions in hospital care (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, the need to move away from a purely volume-driven system in favor of a more value-driven one began to emerge in the area of health services management. This meant focusing more on the quality of care than its volume ( 1 ).…”
Section: Introductionmentioning
confidence: 99%